‘Just saying it like it is’: A comparative study on the characterizations of Chris Christie and Donald Trump as 'tough-guy' politicians - Bourgeois, Samuel (SAGE Publications, 2025)
This article pursues two main research aims. First, it examines how two politicians running for president in 2016 strategically drew on stereotypical tropes of Metropolitan New Yorkers to characterize themselves as brash and argumentative ‘tough guys’ from New York City and North New Jersey respectively in an effort to project strength and effectiveness as leaders. Second, it tests the extent to which Donald Trump’s abrasive persona was truly unique and norm-breaking upon his entrance into politics. Through comparative case studies of Trump and New Jersey Governor Chris Christie – both known for characterizing themselves as New York/New Jersey tough guys during the 2016 Republican primaries – this study examines their rhetorical styles prior to and during the 2016 primary debates. While both figures attracted attention for their impoliteness and blunt speech, only Trump successfully translated this into political success in the primaries and general election alike. While Christie’s brash rhetorical use of impoliteness maintained an image closely tied to that of a New Jersey tough guy, Trump’s tough-guy persona became increasingly idiomatic as his career developed from the 2000s. Moreover, Trump is found to use impoliteness strategies that are more gratuitously face-aggravating and ad hominem in nature. The data therefore confirms that Trump indeed entered politics as a more brash, offensive and norm-challenging politician even when compared to others, including those from his home region.
Keywords: American political rhetoric; characterization; Chris Christie; Donald Trump; impoliteness